The Current situation of Child and adolescent psychological problems and intervention in China - Jiao, Wenyan; Liu, Lin; Li, Rui; Zhao, Na (Asian Journal of Medical Sciences, 2016)
In China, the psychological health problems of children and adolescents have been more and more serious recently. The psychological disorders not only have a lot of adverse effects for children and adolescents, but also were an important source of mental disease in adulthood. In order to make more people understand this serious problem, this paper summarized the current situation of child and adolescent mental health problems in China and the risk factors for child and adolescent mental health problems; additionally, the interventions of child and adolescent psychological problems were also reviewed in this paper. Asian Journal of Medical Sciences Vol. 7(3) 2016 15-17